PENGARUH VARIASI KADAR AMILUM GARUT (Maranta arundinaceae Linn) SEBAGAI BAHAN PENGIKAT TERHADAP SIFAT FISIK DAN KIMIA TABLET PARASETAMOL - Sugiyono Sugiyono; Pipit Murdiyani; Yulias Ninik Windriyati (Universitas Wahid Hasyim Semarang, 2012)
ABSTRACT Starch had a characteristic that could be used as a binder. Arrowroot starch containing amylose and amylopectin which could be used as a binder. Paracetamol had the flow properties and compactibility badly, it was necessary to make granules by wet granulation method (Voigt, 1984). This study aimed to determine the influence of variations in levels of arrowroot starch as a binder to the physical and chemical properties of paracetamol tablets. This research was conducted by mixing paracetamol with mucilago amylum arrowroot (FI: 5%, FII: 7.5%, FIII: 10%, FIV: 12.5%, and FV: 15%) and were given lactose, sifted, and dried. Granules sifted back, plus primogel and magnesium stearate. Mixed granules tested flow rate, rupose angle and tapping index . The granules was then into tablet and then their physical properties were observed, including weight uniformity, hardness, brittleness, and dissolving time.The active substance content was decided based on Farmakope Indonesia Edisi III. The data gathered were then analyzed theoretically by comparing then against what were stated in the literature and statistic cally tested by using one way ANAVA with a confidence degree of 95%, which was then furthered by using the Tuckey test. The result that the starch contained in the arrowroot could be used as a paracetamol tablet binder. Tablets of all formulas met the requirements of a good tablet physical properties. Hardness and tablet disintegration time increased with increasing levels of arrowroot starch as binder, while the fragility of the tablet decreased. Key words: arrowroot amylum, binder, Tablet parasetamol